The immune landscape of fetal chorionic villous tissue in term placenta - Doratt, Brianna M.; True, Heather E.; Sureshchandra, Suhas; Qiao, Qi; Rincon, Monica; Marshall, Nicole E.; Messaoudi, Ilhem (Frontiers in Immunology, 2025)
IntroductionThe immune compartment within fetal chorionic villi is comprised of fetal Hofbauer cells (HBC) and invading placenta-associated maternal monocytes and macrophages (PAMM). Recent studies have characterized the transcriptional profile of the first trimester (T1) placenta; however, the phenotypic and functional diversity of chorionic villous immune cells at term (T3) remain poorly understood.MethodsTo address this knowledge gap, immune cells from human chorionic villous tissues obtained from full-term, uncomplicated pregnancies were deeply phenotyped using a combination of flow cytometry, single-cell RNA sequencing (scRNA-seq, CITE-seq) and chromatin accessibility profiling (snATAC-seq).ResultsOur results indicate that, relative to the first trimester, the frequency of fetal macrophages (HBC, proliferating HBC) is significantly reduced, whereas that of infiltrating maternal monocytes/macrophages (PAMM1b, PAMM1a, PAMM2, MAC_1) increased in T3. PAMM1b and HBCs exhibit the most phagocytic capacity at term highlighting their regulatory role in tissue homeostasis in late pregnancy. The transcriptional profiles of resident villous immune subsets exhibit a heightened activation state relative to the relative to T1, likely to support labor and parturition. Additionally, we provide one of the first insights into the chromatin accessibility profile of villous myeloid cells at term. We next stratified our findings by pre-pregnancy BMI since maternal pregravid obesity is associated with several adverse pregnancy outcomes. Pregravid obesity increased inflammatory gene expression, particularly among HBC and PAMM1a subsets, but dampened the expression of antimicrobial genes, supporting a tolerant-like phenotype of chorionic villous myeloid cells. We report a decline in HBC abundance accompanied by an increase in infiltrating maternal macrophages, which aligns with reports of heightened chorionic villous inflammatory pathologies with pregravid obesity. Finally, given the shared fetal yolk-sac origin of HBCs and microglia, we leveraged an in vitro model of umbilical cord blood-derived microglia to investigate the impact of pregravid obesity on fetal neurodevelopment. Our findings reveal increased expression of activation markers albeit dampened phagocytic capacity in microglia with pregravid obesity.DiscussionOverall, our study highlights immune adaptations in the fetal chorionic villous with gestational age and pregravid obesity, as well as insight towards microglia dysfunction possibly underlying poor neurodevelopmental outcomes in offspring of women with pregravid obesity.